2013
DOI: 10.1002/mnfr.201200504
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nrf2‐dependent gene transcription by bilberry anthocyanins in vivo

Abstract: In a human pilot intervention study (healthy + ileostomy probands), the questions were addressed whether in vivo consumption of an anthocyanin-rich bilberry (Vaccinium myrtillius L.) pomace extract (BE) affects (i) the transcription of Nrf2-dependent genes in peripheral blood mononuclear cells (PBMC), indicative for systemic effects, and (ii) the level of oxidative DNA damage in these cells. In healthy test subjects transcripts of NAD(P)H quinone oxidoreductase 1 (NQO1) were significantly elevated throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 20 publications
5
83
0
2
Order By: Relevance
“…Our data revealed that PGA is a poor neuroprotective agent as this compound was unable to mitigate toxicity induced by hydrogen peroxide, SNP, and glutamate treatment. This was somewhat surprising as recent research using a luciferase reporter assay in CHO cells suggests that PGA is a potent inducer of Nrf2 expression, whereas PCA and cyanidin-3- O -glucoside did not appear to alter Nrf2 expression [52]. Moreover, this study revealed that metabolism of anthocyanins by gut microflora appears to be necessary to observe changes in the expression of Nrf2 effector genes, such as quinone oxidoreductase 1, suggesting that anthocyanin metabolites, particularly PGA, and not anthocyanins themselves, may be responsible for Nrf2 upregulation [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data revealed that PGA is a poor neuroprotective agent as this compound was unable to mitigate toxicity induced by hydrogen peroxide, SNP, and glutamate treatment. This was somewhat surprising as recent research using a luciferase reporter assay in CHO cells suggests that PGA is a potent inducer of Nrf2 expression, whereas PCA and cyanidin-3- O -glucoside did not appear to alter Nrf2 expression [52]. Moreover, this study revealed that metabolism of anthocyanins by gut microflora appears to be necessary to observe changes in the expression of Nrf2 effector genes, such as quinone oxidoreductase 1, suggesting that anthocyanin metabolites, particularly PGA, and not anthocyanins themselves, may be responsible for Nrf2 upregulation [52].…”
Section: Discussionmentioning
confidence: 99%
“…This was somewhat surprising as recent research using a luciferase reporter assay in CHO cells suggests that PGA is a potent inducer of Nrf2 expression, whereas PCA and cyanidin-3- O -glucoside did not appear to alter Nrf2 expression [52]. Moreover, this study revealed that metabolism of anthocyanins by gut microflora appears to be necessary to observe changes in the expression of Nrf2 effector genes, such as quinone oxidoreductase 1, suggesting that anthocyanin metabolites, particularly PGA, and not anthocyanins themselves, may be responsible for Nrf2 upregulation [52]. Given this finding, it is somewhat surprising that PGA did not protect CGNs from oxidative stress; however, this could be due to the fact that primary neurons have a relatively weak Nrf2 response in comparison to other cells in the brain such as astrocytes [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cyanidin and cyanidin-3- O -glucoside are anthocyanins that have been reported to activate the Nrf2 system [10,27]. However, it was not the intact anthocyanins, but a metabolite produced by gut bacteria, phloroglucinol aldehyde, that activated the Nrf2/ARE system in one study [27]. Protocatechuic acid, cyanidin-3- O -glucoside, syringic acid, vanillic acid and gallic acid did not activate the Nrf2/ARE system by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Protocatechuic acid, cyanidin-3- O -glucoside, syringic acid, vanillic acid and gallic acid did not activate the Nrf2/ARE system by themselves. So, one’s ability to activate the Nrf2/ARE system by consuming dietary anthocyanins and other phenolic compounds may depend on having a healthy gut microbiome [27]. …”
Section: Introductionmentioning
confidence: 99%
“…89,90 Moreover, some evidence suggests that these simple phenolics may exert anticancer effects. 91,92 In pilot studies, supplementation of CRC patients with freeze-dried black raspberry (BRB) suppositories and/or oral BRB slurry or an anthocyanin-rich bilberry extract appeared to have a protective effect. 85À87 Over a short period (2À4 weeks) orally supplemented BRB extract was able to significantly reduce proliferation in colon tumors, but crucially not in normal colonic mucosa.…”
Section: Biological Activity and Anticancer Properties Of Berry Fruitsmentioning
confidence: 99%